MemStar: A one‐shot Escherichia coli‐based approach for high‐level bacterial membrane protein production. Issue 20 (28th August 2014) - Lee, Chiara; Kang, Hae Joo; Hjelm, Anna; Qureshi, Abdul Aziz; Nji, Emmanuel; Choudhury, Hassanul; Beis, Konstantinos; de Gier, Jan-Willem; Drew, David
Abstract : Optimising membrane protein production yields in Escherichia coli can be time‐ and resource‐consuming. Here, we present a simple and effective Mem brane protein S ingle sho t a mplification r ecipe: MemStar. This one‐shot amplification recipe is based on the E. coli strain Lemo21(DE3), the PASM‐5052 auto‐induction medium and, contradictorily, an IPTG induction step. Using MemStar, production yields for most bacterial membrane proteins tested were improved to reach an average of 5 mg L −1 per OD600 unit, which is significantly higher than yields obtained with other common production strategies. With MemStar, we have been able to obtain new structural information for several transporters, including the sodium/proton antiporter NapA. Abstract : MemStar is an E. coli ‐based Mem brane protein S ingle sho t a mplification r ecipe. The average MemStar production yield is ∼5mgL −1 per OD600 unit. Increased membrane protein production per cell decreases detergent costs. MemStar increases the number of feasible targets for X‐ray crystallography.